Post-Imaging Arrow Markers On X-Rays: A Simple Tool To Enhance Fracture Localization - Khan, Hammad; Mir Abdul Basit; Kashani, Syed Darian (Journal of the Pakistan Medical Association, 2025)
Sir/Madam, Radiology plays a key role in the diagnosis, treatment, and follow-up assessments of trauma patients. Precise interpretation of imaging, particularly plain x-ray, is fundamental for making appropriate clinical decisions. However, in crowded emergency departments or in settings with limited resources without digital annotation tools, subtle or non-displaced fractures can be easily missed or difficult to relocate on follow-ups or during multi-disciplinary reviews. In radiology, errors and discrepancies are quite common, with an estimated rate of 3 to 5% on daily basis, and even higher rates have been reported in some targeted studies. These errors can arise from a wide range of human and system-related factors [2]. To overcome this, I would like to propose a simple yet practical technique to enhance fracture localization on radiographs; using a black marker to draw arrow indicators directly on the printed x-ray film after image has been taken. Marking a visible arrow pointing to the fracture site can markedly improve clarity, minimizes the time needed for reinterpretation, and improves communication among healthcare teams. Additionally, it supports junior doctors and students in learning and recognizing relevant pathology more confidently. This approach aligns with a wider goal of minimizing diagnostic errors and enhances communication in radiology. As highlighted by Berlin, effective and clear communication of imaging findings is essential for achieving optimal outcomes [1]. Additionally, Brady has noted, reducing errors in radiology frequently depends on simple, practical strategies that make the findings more visible [2]. Due to its simplicity, zero cost, and practical value, this method has the potential for broader adoption particularly in trauma radiology and in settings with limited resources.